2019
DOI: 10.1111/jgs.16219
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for (Discontinuation of) Statin Treatment in Older Adults: Review of Guidelines

Abstract: OBJECTIVES: As a person's age increases and his/her health status declines, new challenges arise that may lead physicians to consider deprescribing statins. We aimed to provide insight into recommendations available in international cardiovascular disease prevention guidelines regarding discontinuation of statin treatment applicable to older adults. DESIGN: We systematically searched PubMed, EMBASE, EMCARE, and the websites of guideline development organizations and online guideline repositories for cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Despite higher rates of discontinuation in nursing homes residents with a limited life expectancy and evidence that life expectancy has been considered when deprescribing statins, 15,16 we still found that over half of those with a prognosis less than six months remained on statins after their nursing home admission. A growing body of evidence suggests that older adults with a limited life expectancy are unlikely to benefit from statins 3,17,37 and could potentially be harmed from continued use.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Despite higher rates of discontinuation in nursing homes residents with a limited life expectancy and evidence that life expectancy has been considered when deprescribing statins, 15,16 we still found that over half of those with a prognosis less than six months remained on statins after their nursing home admission. A growing body of evidence suggests that older adults with a limited life expectancy are unlikely to benefit from statins 3,17,37 and could potentially be harmed from continued use.…”
Section: Discussionmentioning
confidence: 67%
“…4 Currently, the few national guidelines on statin prescribing (and deprescribing) for older adults, older than 75 years, are inconsistent. 16,39 Part of the issue underlying inconsistent guidelines is likely the insufficient availability of evidence on the efficacy and safety of statins in older adults. Clinical trials on treatment of CVD have historically excluded older adults.…”
Section: Potential Mechanisms and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, discussions may arise as to what to monitor and how frequently to monitor in elderly populations, especially when the frail and vulnerable elderly with short life expectancy are taken into account. For example, it can be argued that the measurement of blood glucose is still necessary in the (frail) elderly to prevent short-term complications, whereas the monitoring of blood lipids seems less necessary, given its association with longer-term complications in a population with a short life expectancy [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, future studies could explore the possibility of developing a clinical deprescribing trial framework to guide future trials. On the deprescribing of statins, more high-quality evidence is needed to guide physicians on appropriate treatment for older adults, which may be facilitated through N-of-1 trials, or other robust trial methods [36].…”
Section: Discussionmentioning
confidence: 99%